A novel Sn2Nb2O7/defective carbon nitride heterojunction photocatalyst: preparation and application for photocatalytic oxytetracycline removal. Issue 22 (20th May 2022) - Zhang, Haoyu; Peng, Liman; Li, Huawei; Su, Yiguo; Huang, Shushu
Abstract : The construction of a traditional type-II Sn2 Nb2 O7 /defective carbon nitride (Sn2 Nb2 O7 /HCN) heterojunction photocatalyst achieved exceptional photocatalytic oxytetracycline degradation performance. Abstract : A traditional type-II Sn2 Nb2 O7 /defective carbon nitride (HCN) heterojunction structure photocatalyst was constructed to enhance the photocatalytic property of the pyrochlore Sn2 Nb2 O7 . Experimental analysis verified that a built-in electric field was formed between Sn2 Nb2 O7 and HCN, resulting in the photogenerated electrons and holes gathering on the conduction band of HCN and valence band of Sn2 Nb2 O7, respectively. The formation of Sn2 Nb2 O7 /HCN improved the separation efficiency and transfer rate of photogenerated charge carriers. The optimal photocatalytic oxytetracycline (OTC) removal efficiency of Sn2 Nb2 O7 /HCN was 58.4% after 150 min of visible light irradiation, which was 1.41 and 1.92 times higher than those of Sn2 Nb2 O7 (41.5%) and HCN (30.4%), respectively. The trapping active species and electron paramagnetic resonance results proved that the dominant active species in the photodegradation of OTC were photogenerated holes, hydroxyl radicals and superoxide anions. This work might provide a new strategy for improving the photocatalytic performance of Sn2 Nb2 O7 by building traditional type-II heterojunction photocatalysts.